A plant bunyaviral protein disrupts SERRATE phase separation to modulate microRNA biogenesis during viral pathogenesis - Jing Zou; Shuai Zhang; Ying Chen; Chun He; Xin Pan; Yimin Zhang; Jianwei Xu; Lijia Zheng; Hongxin Guan; Ming Wu; Dongqi Xie; Yinghua Ji; et al. (Nature Communications)
Abstract Liquid-liquid phase separation (LLPS) regulates diverse biological functions by mediating the assembly of biomolecular condensates. However, it remains unclear how host LLPS is targeted by viruses during infection. Here we show that a plant bunyaviral protein, the disease-specific protein (SP) encoded by rice stripe virus (RSV), possesses phase separation potential through its N-terminal intrinsically disordered region 1 (IDR1). In vivo, however, SP does not form phase-separated biomolecular condensates independently but utilizes its phase separation properties to interfere with the phase separation of the SERRATE protein (SE), a key component of Dicing bodies essential for microRNA processing. By disrupting SE phase separation, SP inhibits D-body assembly and miRNA biogenesis. Our study demonstrates that a viral protein can modulate host microRNA processing by targeting LLPS, revealing a previously uncharacterized mechanism involved in viral infection strategies and miRNA biogenesis regulation in plants.